Botulinum Toxin for Asians - Seo, Kyle K.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book, containing more than 400 photos and illustrations, provides practical guidelines for the cosmetic use of botulinum toxin type A (BTA) in Asians. The differences in BTA treatment of Asians and Caucasians with respect to applicable dose, injection methods, anatomic significance, and indications are clearly described. It is explained how the optimal dose and injection sites for the treatment of wrinkles differ from the guidelines advocated in North America and Europe. Detailed consideration is given to the rapidly expanding role that BTA treatment is playing in facial and body contouring based on leveraging the mechanism of disuse muscle atrophy. Examples that are particularly relevant in Asians include treatment of hypertrophy of the masseter and temporalis muscles and calf muscle reduction. Further chapters are devoted to the use of BTA in the treatment of hyperhidrosis and the intradermal injection of BTA. The book will be an excellent resource for all dermatologists, plastic surgeons, cosmetic Physicians, and other clinicians who employ BTA in Asian patients. .
Chapter 1. Introduction to botoxology -- Chapter 2. Botulinum for wrinkle treatment -- Chapter 3. Botulinum facial contouring -- Chapter 4. Botulinum body contouring -- Chapter 5. Botulinum intradermal injection -- Chapter 6. Botulinum for hyperhidrosis treatment.
Keywords: Medicine; Dermatology; Plastic surgery; Medicine & Public Health; Dermatology; Plastic surgery